Biografi Pendidik Djiwa Duarsa sebagai Refleksi Program Pertukaran Siswa SPGN Se-Jawa dan Bali 1980-an - I Ketut Ardhana; I Nyoman Suparwa; Ida Ayu Gde Yadnyawati; Fransiska Dewi Setiowati Sunaryo (Universitas Udayana, 2023)
In recent years, the Freedom to Learn and Freedom Campus (MBKM) initiative have been vigorously implemented. These include activities such as internships and student exchanges. While the Freedom to Learn program must be welcomed, it is important to note that some forms of this program are not entirely new, as student exchanges have been conducted at the high school level before. This article outlines the Student Exchange Program (PPS) through the biographical account of a legendary educator from Bali, Wayan Djiwa Duarsa, who founded and led State Teacher Education School (SPGN) Denpasar for 27 years (1959-1986). Data was collected through interviews, focused group discussions, and document studies. The analysis results indicate that in the early 1980s, Djiwa Duarsa pioneered the Student Exchange Program across Java and Bali, aiming to broaden the understanding of the archipelagic values among students and instill a sense of nationalism. In addition to the monumental PPS program, Djiwa Duarsa's biography also depicts the history of SPGN in Bali and its achievements at the national level. This article is expected to contribute to providing an initial study on the history of teacher education in Bali, which is useful for improving the quality of education for the progress of the nation.